Comparison of the dynamic characteristics of piezoceramic actuators used in vibration diagnostics of large-scale structures - Shardakov, Igor′ Nikolayevich; Shestakov, Aleksey Petrovich; Glot, Irina Olegovna; Gusev, Georgiy Nikolayevich; Epin, Valeriy Valer′yevich; Tsvetkov, Roman Valer′yevich (Computational Continuum Mechanics, 2024)
One of the effective methods of non-destructive testing of large-scale structures is active vibration diagnostics. It involves local dynamic impact on the structure and recording structural vibration response. Analysis of a set of responses recorded at different points allows determining the mechanical condition of an object under study. According to the method of active vibration diagnostics, dynamic influences are realized by special devices – actuators. Today, most widely used are piezoceramic actuators. As a rule, they are a piezoceramic plate embedded in the structure or located on its surface. Previously, the authors have proposed a piezoceramic actuator with attached mass, which is able to create more intense impact on the structure. In this work, numerical modeling is applied to evaluate the effectiveness of a modified device in comparison with traditional devices using a concrete slab and a model 4-story building as examples. Based on the results obtained, it is concluded that the elastic waves, excited by the actuators of three types mentioned here, are of significantly different intensity. The piezoceramic plate placed on the surface of the structure provides the wave with the lowest amplitude. It is 1.9 times smaller than for the plate embedded in the structure and 12 times smaller than for the plate with attached mass. The numerical experiment, which demonstrates the propagation of an elastic wave in the components of the model building, made it possible to evaluate the intensity of vibrations at different distances from a vibration source. For the actuator with attached mass, the amplitude of acceleration at the point placed at a distance of 1.7 meters from the actuator is 20 m/s2; 5.2 meters – 5 m/s2; 8.7 meters – 2 m/s2. These accelerations can be reliably measured by most modern accelerometers. Thus, a piezoceramic actuator with attached mass is the most promising device for active vibration diagnostics of large-scale concrete structures. The use of such actuators in the monitoring system reduces the total number of actuators and sensors due to increasing the distance between them.
Keywords: monitoring; nondestructive testing; vibration diagnostics; actuator; piezoceramics; numerical modeling